2017
DOI: 10.1016/s2214-109x(17)30043-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the 13-valent pneumococcal conjugate vaccine against invasive pneumococcal disease in South African children: a case-control study

Abstract: Gavi, The Vaccine Alliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 18 publications
3
42
0
Order By: Relevance
“…Regardless, PCV7 caused >85% reduction in IPD in South Africa, crucially in HIV-infected individuals [5]. Consistent with findings in high-income countries [6], higher-valent PCVs appears to be highly effective in reducing VT serotypes in carriage (>65%) and IPD (>80%) in Africa[79].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Regardless, PCV7 caused >85% reduction in IPD in South Africa, crucially in HIV-infected individuals [5]. Consistent with findings in high-income countries [6], higher-valent PCVs appears to be highly effective in reducing VT serotypes in carriage (>65%) and IPD (>80%) in Africa[79].…”
Section: Introductionmentioning
confidence: 67%
“…In addition to reducing IPD [2, 8, 9], PCV has an added benefit of reducing VT carriage [10]. However, the impact on overall carriage rate and density is not substantial [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Disappointingly, introduction of the broader vaccine did not further improve ear health. The vaccine efficacy for prevention of invasive disease has been proven [58, 59]. Although thoroughly studied regarding several aspects, including OM, there is at present a lack of knowledge on the specific effects of PCV on rAOM.…”
Section: Preventionmentioning
confidence: 99%
“…Studies in sub-Saharan Africa have reported varied measures of vaccine effectiveness and impact. Overall, there is overwhelming evidence of effectiveness against invasive pneumococcal disease with significant decline in disease after introduction of the vaccine (25–29).…”
Section: Introductionmentioning
confidence: 99%